Kontribusi Terapi Dzikir dalam Pemulihan Pasien dengan Gangguan Sensori Persepsi: Halusinasi Pendengaran - Arifin, Nur Afni Wulandari; Fresia, Sinta; Astuti, Harwina Widya; Novita, Sherliana (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims to determine the effectiveness of psychoreligious therapy: dhikr in reducing the signs and symptoms of auditory hallucinations. This descriptive case study method involved 2 patients who had signs and symptoms of auditory hallucinations. Participants were given psychoreligious therapy by saying Allahu Akbar, Lailahailaallah, Alhamdulillah, Subhanallah 33 times for 10-20 minutes. The results of the study showed that there was a decrease in the score of signs and symptoms of hallucinations in client I and client II. Before implementing dhikr therapy, client I had 6 signs and symptoms of hallucinations while client II had 4 signs and symptoms of hallucinations. After being given dhikr therapy intervention, client I's signs and symptoms of hallucinations were 3 while client II's were 1. Conclusion, psychoreligious therapy: Dhikr is effective in reducing signs and symptoms in patients with auditory hallucinations. Keywords: Auditory Hallucinations, Psychoreligious Therapy: Dhikr, Sensory Perception Disorders, Background: A person who experiences hallucinations will feel false sensations such as sound, touch, taste, smell or sight. Efforts that can be made by nurses in dealing with patients with percussion sensory disorders: hallucinations apart from applying generalist therapy by identifying hallucinations, teaching how to rebuke, complying with taking medication, teaching how to talk to other people when hallucinations appear, and carrying out scheduled activities can be implemented psychoreligious therapy: dhikr. Dhikr therapy aims to enable patients to focus attention (khusyu') by remembering the greatness and oneness of Allah. Objective: To find out how effective psychoreligious therapy: Dhikr is in reducing the signs and symptoms of hallucinations in patients. Method: This research uses descriptive observational with a case study approach. The number of samples in this study was 2 people. Clients are taught to say Allahu akbar, Lailahailaallah, Alhamdulillah, Subhanallah 33 times for 10-20 minutes. The results of the study showed that the signs and symptoms of hallucinations in client I before implementation had a score of 6 signs of hallucinations and after being given the intervention had a score of 3 and client II before implementation had a score of 4 signs of hallucinations and after being given the intervention had a score of 1. This intervention was given for 3 days with a time duration adjusted to the frequency of hallucinations for each respondent. Conclusion: Psychoreligious therapy (dhikr) is effective in reducing signs and symptoms of auditory hallucinations. The client knows that the action that must be taken is dhikr and does so to divert attention from the hallucinations. Keywords: Sensory perception disorders, auditory hallucinations, psychoreligious therapy: dhikr